Quality of life after surgical treatment of head and neck paragangliomas - Sauter, Christina Julia; Erhart, Philipp; Böckler, Dittmar; Schuler, Patrick; Plinkert, Peter K.; Hohenberger, Ralph (Head & neck, 2025)
Background Head and neck paragangliomas (HNPGLs) are rare neuroendocrine tumors and often arise in the head and neck. Due to their localization, the tumor and its surgical treatment pose a risk for cranial nerve impairments. Few studies have focused on the health-related quality of life (HRQOL) in patients with HNPGLs and their relation to tumor localization. Methods In patients (n = 125) treated with primary surgery for HNPGLs between 2006 and 2023, clinical data was obtained. Long-term QOL was assessed with the validated German version of the EORTC QLQ-H&N43 with a mean follow-up since surgery of 6.0 years. Results Most common were carotid body PGLs (n = 78; 62.4%) including Shamblin I (n = 25), II (n = 42) and III (n = 9) along jugular (n = 31; 24.8%) and vagal (n = 10; 8.0%) tumors. In the QLQ-H&N43, the scales fear of progression (41.2), coughing (33.9), neurological problems (22.4), sexuality (21.4), and swallowing (21.2) showed the highest mean scores. Jugular and vagal tumors showed higher symptom levels compared to carotid body tumors, especially Shamblin I. Conclusions Surgical treatment of PGLs may lead to significant impairments in physical and psychological domains, especially in larger carotid body, vagal and jugular tumors. Structured pre- and postoperative cranial nerve examinations and interprofessional support should be provided to mitigate postoperative QOL reduction.
Online veröffentlicht: 6. November 2025
Gesehen am 26.01.2026